Louis J. Dupree, A Digest of the Ordinances of the City Council of Memphis, from the Year 1826 to 1857 Together with All Acts of the Legislature of Tennessee Which Relate Exclusively to the City of Memphis, with an Appendix Page 161, Image 161 (1857) [Ordinances of the City of Memphis, Pistols and Guns, § 1. - (:unkn) unknown (General Publisher, 1857)
It shall be unlawful for any person to fire any pistol, gun or other firearm within the limits of this city, unless it be on the occasion of a military parade,
--
Keywords: DISCHARGE